2016
DOI: 10.1142/s0192415x16500324
|View full text |Cite
|
Sign up to set email alerts
|

Astragalus saponinsInhibits Lipopolysaccharide-Induced Inflammation in Mouse Macrophages

Abstract: Excessive nitric oxide (NO) and pro-inflammatory cytokines are produced during the pathogenesis of inflammatory diseases and cancer. It has been demonstrated that anti-inflammation contributes Astragalus membranaceus saponins (AST)'s beneficial effects in combination of conventional anticancer drugs. However, the immunomodulating property of AST has not been well characterized. In this study, we found that AST suppressed lipopolysaccharide (LPS)-induced generation of NO without causing cytotoxicity in the mous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 22 publications
3
20
0
Order By: Relevance
“…Among them, TS suppressed the production of TNF-α, IL-1β, iNOS and NO more effectively, while the treatments with TP and TF resulted in relatively significant reduction in the levels of COX-2 and PGE2, respectively. The findings are in agreement with the previous works [3237]. For instance, astragalus saponins inhibited the production of TNF-α, the overexpression of iNOS and the subsequent generation of NO in lipopolysaccharide (LPS)-stimulated mouse macrophage RAW264.7 [32].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Among them, TS suppressed the production of TNF-α, IL-1β, iNOS and NO more effectively, while the treatments with TP and TF resulted in relatively significant reduction in the levels of COX-2 and PGE2, respectively. The findings are in agreement with the previous works [3237]. For instance, astragalus saponins inhibited the production of TNF-α, the overexpression of iNOS and the subsequent generation of NO in lipopolysaccharide (LPS)-stimulated mouse macrophage RAW264.7 [32].…”
Section: Discussionsupporting
confidence: 93%
“…The findings are in agreement with the previous works [3237]. For instance, astragalus saponins inhibited the production of TNF-α, the overexpression of iNOS and the subsequent generation of NO in lipopolysaccharide (LPS)-stimulated mouse macrophage RAW264.7 [32]. In the same model, astragalus flavonoids reduced the release of TNF-α, IL-1β and NO in a dose-dependent manner [33].…”
Section: Discussionsupporting
confidence: 92%
“…These results are likely due to the specific functions of various bioactive substances present in AMSL, such as saponins, including astragaloside; flavonoid, including isoquercitrin; and astragalus polysaccharides. A large number of studies have shown that these components contained in AMSL have various important physiological functions, including immunomodulatory (Du et al, ; Wang, Ren, et al, ), antioxidative (Shahzad, Shabbir, Wojcikowski, Wohlmuth, & Gobe, ), antiaging (Li et al, ), antifatigue (Kuo, Tsai, Loke, Wu, & Chiou, ), and antibacterial activities (Wang, Han, Dai, Wang, & Ao, ).…”
Section: Discussionmentioning
confidence: 99%
“…Some of those studies were conducted with extracts enriched by specific class of compounds such as flavonoids, saponins or glycosides, therefore evaluation of the fractions of A. jolderensis seems to be valued. [18][19][20][31][32][33] In addition, C. commutatus extract inhibited NO production in stressed cells at all implied concentrations. Cytotoxic effect was not detected in the unstressed cells either in the present or in the previous study on this extract, however, it lowered the cell viability during the stress condition.…”
Section: Discussionmentioning
confidence: 99%
“…are hepatoprotective, immunostimulant and antiviral effects, and recent researches revealed promising positive effects of various Astragalus species in oxidative stress and inflammation. [18][19][20][21] In addition, researches revealed that Astragalus polysaccharides from Astragalus melittin protects against injuries of coxsackievirus B3-induced myocardial damage and inflammation. 22 Besides, the Convolvulaceae family, especially the genus Convolvulus, has a large number of medicinal plants and some species like C. arvensis, C. austro-aegypticus, C. pilosellifolius are widely used in folklore medicine of Asia and Africa.…”
Section: Introductionmentioning
confidence: 99%